Pengaruh Permainan Tradisional Galah Asin terhadap Peningkatan Kelincahan Siswa Kelas V SD - Liondi Pranklin Sitanggang; Janwar Frihasan Sinuraya; Aser Paul Nainggolan (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
The low level of agility among elementary school students has become an important issue in Physical Education, Sports, and Health (PJOK) learning, particularly due to the limited variation in instructional methods and the decline in students’ physical activity in the digital era. This condition causes students to be less physically active, resulting in underdeveloped abilities in changing direction, body coordination, and movement balance. This study aimed to determine the effect of the traditional Galah Asin game on improving the agility of fifth-grade students at SD Swasta Advent Barusjulu. The research employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest Design. The research sample consisted of 37 students selected through the total sampling technique. Data were collected using a 4x10 meter shuttle run test to measure students’ agility levels before and after the treatment. The findings revealed that the average pretest score of 25.63 seconds decreased to 22.41 seconds in the posttest, indicating an improvement difference of 3.22 seconds. The paired sample t-test results showed that the calculated t-value of 9.87 was greater than the t-table value of 2.045 with a significance level of p < 0.000, indicating that the traditional Galah Asin game had a significant effect on improving students’ agility. The game was proven to enhance agility skills, active participation, learning motivation, and students’ social interaction during PJOK learning activities. The novelty of this study lies in the utilization of the traditional Galah Asin game as a local culture-based PJOK learning strategy that not only improves students’ agility but also supports cultural preservation and strengthens elementary school students’ physical activity in the modern era.